2016
DOI: 10.1093/jjco/hyw055
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive video-assisted lateral neck lymphadenectomy for the papillary thyroid carcinoma with cervical lymph nodes metastasis

Abstract: Objective: Minimally invasive video-assisted technique has been successfully used in thyroidectomy to treat low-and intermediate-risk papillary thyroid cancer. But there was very little experience of this technique to be used in the lateral neck lymphadenectomy to treat papillary thyroid cancer with lateral neck lymph node metastasis. This study aimed to verify the potential benefits of a new minimally invasive video-assisted lateral neck lymphadenectomy that evaluated the likelihood of the surgical method as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Since lymph nodes metastasis is a critical predictive factor in thyroid carcinoma [21,22], we further analyzed the relationship between differentially expressed lncRNAs and lymph nodes 9754 metastasis. Among 352 differentially expressed lncRNAs, we found that 4 upregulated genes (LINC01016, LHX1-DT, IGF2-AS, and MIR1-1HG-AS1) were significantly expressed across patients with N1 than N0 (Table 4), and the results were visualized by heatmap ( Figure 7).…”
Section: Lymph Nodes Metastasis-related Lncrnasmentioning
confidence: 99%
“…Since lymph nodes metastasis is a critical predictive factor in thyroid carcinoma [21,22], we further analyzed the relationship between differentially expressed lncRNAs and lymph nodes 9754 metastasis. Among 352 differentially expressed lncRNAs, we found that 4 upregulated genes (LINC01016, LHX1-DT, IGF2-AS, and MIR1-1HG-AS1) were significantly expressed across patients with N1 than N0 (Table 4), and the results were visualized by heatmap ( Figure 7).…”
Section: Lymph Nodes Metastasis-related Lncrnasmentioning
confidence: 99%
“…Among studies with at least 12 months of follow-up, there were no reported recurrences, sTg levels were low or undetectable, and there were no differences in postoperative complications between groups, including transient hypocalcemia or hoarseness, Horner's, seroma, hematoma, wound infections, or chyle leak (32)(33)(34)(35)(36). There were no cases of permanent RLN injury or hypocalcemia in the studies.…”
Section: Outcomes and Complicationsmentioning
confidence: 89%
“…Among studies, the mean LN yield was 25-41, except in two studies that had a much lower yield of 8.3 (range 3-21) and 8.5 (range 8-9) (30)(31)(32)(33)(34)(35)(36)(37)(38). Mean operative time for VASLND alone was 46-60 minutes, but when included with thyroidectomy and CND, mean operative times were 198-220 minutes (30)(31)(32)(33)(34)37).…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
See 2 more Smart Citations